ASSESMENT OF THE DNA BARCODES CHARACTERISTIC AND EVALUATION OF PHYLOGENETIC RELATIONSHIP OF Castanopsis argentea (Blume) A. DC. - Chika, Syifara; Zahro, Shofiyyatuz (Berita Biologi, 2024)
Castanopsis, the third largest genus under Fagaceae, is widespread in tropical and subtropical areas in East and South Asia. This plant is one of the woody plants that has the potential to be developed because it is helpful for wildlife for nesting and is used in land reforestation activities. Based on data from the Red List of the International Union for the Conservation of Nature and Natural Resources (IUCN), it is reported that the Castanopsis argentea species is threatened with extinction. Research based on genetic aspects of this species is also rarely carried out. This research aims to conduct an in silico study and analyze the kinship relationships of Castanopsis argentea. The method used in this research is the in silico method, which takes Castanopsis argentea nucleotide data from NCBI in the matK region. Based on this research, the phylogenetic results show that the results of the phylogenetic tree reconstruction show that the matK region is divided into two ingroup clades and one outgroup. The matK region in Castanopsis argentea is highly conserved because it only has three genetic variations namely N282T, C285T, and C422A. In this study, the matK gene can group species from the same genus and separate species from different genus. This is in line with the results of the phylogenetic tree, which shows that members of the same genus successfully grouped into one clade. More research on DNA barcoding of Castanopsis argentea must be carried out and developed because more genetic data still needs to be collected at NCBI. The genetic data of a species is essential to research and is stored in NCBI's Genbank for genetic conservation purposes.